The Supply of Child Care Labor - Blau, David M. (Journal of Labor Economics, 1993)
This article presents estimates of the elasticity of supply of labor to child care. This parameter is an important determinant of the effects of child care subsidies and regulations on the cost of child care. Using data from the Current Population Survey, there is evidence of an elasticity in the range of 1.2-1.9. This implies that the majority of the benefits of child care subsidies accrue to consumers of child care. It is also consistent with the fact that child care workers' wages remained flat in real terms in recent years, despite rapid growth in the demand for child care.